2021
DOI: 10.1080/1828051x.2021.1886002
|View full text |Cite
|
Sign up to set email alerts
|

Lactation performance of Awassi ewes fed diets containing either Atriplex halimus L. or olive cake

Abstract: The objective of the two studies was to evaluate t effects of feeding on lactating Awassi ewes (study 1) and lambs (study 2), fed on a diet of Atriplex halimus L. (ATR) or olive cake (OC), as a foraging source substitute for wheat straw. In study 1, 33 newly lambed ewes and their lambs were randomly assigned one of three diets: The control diet (CON), 250 g/kg of OC, or 250 g/kg of ATR dry matter (DM). Ewes and lambs were housed in individual pens. Ewes fed CON diet had greater DM, neutral detergent fibre, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…The cost of gain decreased with the FB200 diet compared to the CON diet, which may be due to the lower price of FB compared with the cost of barley grains and soybean meal during the study period. Many studies dealing with alternative feeds from plant or agro-industrial by-products, such as sweet lupin [ 21 , 22 ], olive cake [ 23 ], black cumin meal [ 3 ], and olive cake and Atriplex halimus L. [ 2 ], obtained similar results by providing diets that were more economically feasible and beneficial to livestock production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost of gain decreased with the FB200 diet compared to the CON diet, which may be due to the lower price of FB compared with the cost of barley grains and soybean meal during the study period. Many studies dealing with alternative feeds from plant or agro-industrial by-products, such as sweet lupin [ 21 , 22 ], olive cake [ 23 ], black cumin meal [ 3 ], and olive cake and Atriplex halimus L. [ 2 ], obtained similar results by providing diets that were more economically feasible and beneficial to livestock production.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the lack of pastures in arid and semi-arid areas is challenging for livestock producers, especially sheep farmers. The high prices of feed ingredients (e.g., barley, wheat, and soybeans) forced livestock keepers and researchers to search for high-quality alternative feed materials that are less expensive [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may be because the price of LUP was lower than the cost of barley grains and soybean meals during the study time. Similarly, many research studies dealt with alternative feeds from plant or agro-industrial by-products, such as sweet lupin [10,11], olive cake [31], olive cake, and Atriplex halimus L. [7] obtained the same results, which provided diets that were more economically feasible and beneficial to livestock production.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the governments greatly reduced subsidies to farmers with cheap feed, which reduced the profits of these farmers [6]. Therefore, the best solution to the problem of the scarcity and high cost of feeds is the use of alternative feeds [5,7]. The use of alternative feeds is beneficial to reduce the cost of feed and is also useful in reducing contamination of agricultural wastes [8].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of OC at 32.3% attenuated the voluntary intake of feed by lamb, as the intake was higher among the control group compared to the OC group (Vera et al, 2013). (Aljamal et al, 2021) reported that DM intake decreased when lactating Awassi ewes were fed OC at 25% compared with ewes fed the control diet. Similar results were reported when high levels of OC were fed to ewes (up to 49% of the diet) (Abbeddou et al, 2011;Beken and Sahin, 2011;Cabiddu et al, 2004;Sadeghi et al, 2009).…”
Section: Dry Matter Intake and Nutrient Digestibilitymentioning
confidence: 98%